2010
DOI: 10.1080/03670244.2010.524102
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Prepared Food Sources in Low-Income Neighborhoods of Baltimore City

Abstract: The food environment is associated with obesity risk and diet-related chronic diseases. Despite extensive research conducted on retail food stores, little is known about prepared food sources (PFSs). We conducted an observational assessment of all PFSs (N = 92) in low-income neighborhoods in Baltimore. The most common PFSs were carry-outs, which had the lowest availability of healthy food choices. Only a small proportion of these carry-outs offered healthy sides, whole wheat bread, or entrée salads (21.4%, 7.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 59 publications
0
54
0
Order By: Relevance
“…An example of a problem for which it is difficult to identify the root cause is the lack of nutritious food options in low-income urban areas. 11,12 A shortage of apples on a farm, for instance, may decrease the apple supply and increase the cost for storeowners to stock apples. As a result, perhaps only larger supermarkets can afford the added cost of stocking the apples, as opposed to smaller grocers in marginalized communities.…”
Section: What Is a System?mentioning
confidence: 99%
“…An example of a problem for which it is difficult to identify the root cause is the lack of nutritious food options in low-income urban areas. 11,12 A shortage of apples on a farm, for instance, may decrease the apple supply and increase the cost for storeowners to stock apples. As a result, perhaps only larger supermarkets can afford the added cost of stocking the apples, as opposed to smaller grocers in marginalized communities.…”
Section: What Is a System?mentioning
confidence: 99%
“…Powell et al [39] found significantly fewer restaurants available in predominantly Hispanic neighborhoods, which had 60.9 % the number of available full-service restaurants and 55.8 % the number of fast-food restaurants compared to non-Hispanic neighborhoods. However, information about the availability and cost of healthy options in restaurants in predominately Hispanic/Latino neighborhoods is limited [55].…”
Section: Retail Food Environments In African American Neighborhoodsmentioning
confidence: 99%
“…Text messaging, Facebook, and Instagram posts advertised store sessions and encouraged the purchase of promoted products. BHCK worked with owners of carryouts, here, defined as an independently owned limited-service prepared food source with few or no seating area, where patron orders and pays before eating (Lee et al, 2010), to design and hang new menus, to advertise healthier sides, drinks, and entrees with a “fresh” logo. Process findings for these components will be reported elsewhere, but are part of the context of intervention implementation reported in this article.…”
Section: Methodsmentioning
confidence: 99%